The influence of demographic profiles on skin conditions - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan JawaD; Ayob, Ain (2016)
A cross-sectional study design was employed with the aim of assessing cosmetic consumers’ skin condition and to identify the influence of cosmetic consumers’ demographic profile on their skin condition. A total of 551 cosmetic consumers who lived in Kuantan, Pahang, were recruited conveniently. Their skin condition was assessed by using DermaLab® Combo with five different parameters: collagen intensity, elasticity, melanin content, moisture and trans-epidermal water loss. A guideline provided by the DermaLab® Combo manufacturer was used to descriptively analyse cosmetic consumers’ skin conditions. Subsequently, the difference in skin conditions with respect to cosmetic consumers’ demographic profile was analysed via non-parametric test. The results show that cosmetic consumers in this study had high collagen intensity, more elastic skin, low melanin content, insufficient moisture skin and low trans-epidermal water loss value. Regarding the differences between the sample population, gender and age had significant influence towards the parameters, respectively. To conclude, skin conditions among the cosmetic consumers in this study were good in terms of collagen, elasticity and skin barrier function. However, they all had skin that was in fair condition and insufficient skin moisture.